GRDP, Poverty, and Health Budget on Human Development in Riau: A Maqasid Al-Shariah Perspective - Fathurrahman, Ayif; Ananda Fauziah Putri; Nurul Naqiliah Binti Nor Azman; Zulkifli, Siti Maryam Binti (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines the effect of Gross Regional Domestic Product (GRDP), poverty, and health expenditure on the Human Development Index (HDI) in Riau Province during 2016–2022, with an analytical perspective based on maqashid shari’ah. The study employs panel data consisting of time-series (2016–2022) and cross-sectional data from 12 districts/cities, analyzed using the Random Effect Model (REM). The results show that GRDP has a positive and statistically significant effect on HDI (β > 0; p < 0.05), indicating that regional economic growth contributes to improving human development outcomes. In contrast, poverty has a negative and significant effect on HDI (β < 0; p < 0.05), confirming that higher poverty levels hinder human development. Meanwhile, health expenditure does not have a statistically significant effect on HDI (p > 0.05), suggesting inefficiencies or misallocation in public health spending. From the maqashid shari’ah perspective, the positive role of GRDP aligns with the principle of maslahah (public benefit), while the negative impact of poverty reflects the importance of hifz al-maal (protection of wealth) in ensuring welfare. The insignificant effect of health expenditure indicates that the objective of hifz al-nafs (protection of life) has not been optimally achieved in regional policy implementation. The main contribution of this study lies in integrating empirical panel data analysis with an Islamic economic framework, particularly maqashid shari’ah, to provide a more comprehensive evaluation of human development determinants. The novelty of this research is its combined quantitative–normative approach, linking statistical findings with Islamic welfare objectives, which remains limited in regional development studies.